2022
DOI: 10.1111/cts.13251
|View full text |Cite
|
Sign up to set email alerts
|

Predicting citation impact from altmetric attention in clinical and translational research: Do big splashes lead to ripple effects?

Abstract: Publications are commonly used to evaluate the productivity and impact of research programs. Traditional metrics examine publication impact through slowly accumulating academic citations. "Altmetrics" are a new way to describe early publication influence in nonacademic media/community spheres (news, tweets, and blogs). Articles with significant altmetric attention make a big splash of im-How to cite this article: Llewellyn NM, Nehl EJ. Predicting citation impact from altmetric attention in clinical and transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…According to this framework, “big splashes” encompass short‐term altmetric attention (news, blogs, and Twitter) and academic attention (peer faculty recommendations and reader downloads), whereas “ripple effects” encompass long‐term altmetric (policy documents, Wikipedia pages, and patent applications) and academic influence (total citations and RCR). This framework is well‐suited to the recency of this portfolio of publications with our understanding that papers often build influence over many years, even decades, post‐publication date; some metrics manifest relatively early and foreshadow longer‐term impact 43 . To illustrate a sample of highly influential research, we list portfolio articles with the 10 highest RCR scores (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this framework, “big splashes” encompass short‐term altmetric attention (news, blogs, and Twitter) and academic attention (peer faculty recommendations and reader downloads), whereas “ripple effects” encompass long‐term altmetric (policy documents, Wikipedia pages, and patent applications) and academic influence (total citations and RCR). This framework is well‐suited to the recency of this portfolio of publications with our understanding that papers often build influence over many years, even decades, post‐publication date; some metrics manifest relatively early and foreshadow longer‐term impact 43 . To illustrate a sample of highly influential research, we list portfolio articles with the 10 highest RCR scores (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…This framework is well‐suited to the recency of this portfolio of publications with our understanding that papers often build influence over many years, even decades, post‐publication date; some metrics manifest relatively early and foreshadow longer‐term impact. 43 To illustrate a sample of highly influential research, we list portfolio articles with the 10 highest RCR scores (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The correlations between metrics of bibliometrics (i.e., citation counts, FWCI, CB, RCR), altmetrics (i.e., PlumX-Captures, Citations, Usages, Mentions, and Social media), and topic measures (i.e., STPP) were assessed by Spearman Rho correlation coefficients [29,30]. This study is the first CTSA evaluation that formally investigated these correlations using the data source provided by Scopus, contributing to the growing literature on this topic [46][47][48][49].…”
Section: • Correlation Measurementioning
confidence: 99%
“…9 Although many studies have identified factors influencing citability, accurately predicting citation numbers has proved difficult. [10][11][12][13][14][15][16][17][18] Few studies have successfully used information available before publication for this purpose. 19 Recently machine learning techniques have been used to find patterns that predict citation count with some success.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have identified factors influencing citability, accurately predicting citation numbers has proved difficult 101112131415161718. Few studies have successfully used information available before publication for this purpose 19.…”
Section: Introductionmentioning
confidence: 99%